2020
DOI: 10.1111/cxo.12933
|View full text |Cite
|
Sign up to set email alerts
|

The influence of orthokeratology compression factor on ocular higher‐order aberrations

Abstract: Background To investigate the influence of compression factor upon changes in ocular higher‐order aberrations (HOAs) in young myopic children undergoing orthokeratology treatment. Methods Subjects aged between six and < 11 years, with low myopia (0.50–4.00 D inclusive), low astigmatism (≤ 1.25 D), and anisometropia (≤ 1.00 D), were randomly assigned to wear orthokeratology lenses of different compression factors in each eye (one eye 0.75 D and the fellow eye 1.75 D). HOAs were measured weekly over one month of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 33 publications
2
29
2
Order By: Relevance
“…61 | No. 2 | Article 22 | 6 mean change in ocular primary spherical aberration after 2 years of ortho-k treatment was +0.80 μm in the current study compared with +0.51 μm in Hiraoka et al 13 , and +0.34 μm in Kim et al 18 These differences in the change in primary spherical aberration (Z 0 4 ) between the studies may be a result of lens design (given that compression factor appears to influence spherical aberration), 48 ethnicity, or some other factors, and likely explain the different reported associations between eye growth and changes in spherical aberration.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…61 | No. 2 | Article 22 | 6 mean change in ocular primary spherical aberration after 2 years of ortho-k treatment was +0.80 μm in the current study compared with +0.51 μm in Hiraoka et al 13 , and +0.34 μm in Kim et al 18 These differences in the change in primary spherical aberration (Z 0 4 ) between the studies may be a result of lens design (given that compression factor appears to influence spherical aberration), 48 ethnicity, or some other factors, and likely explain the different reported associations between eye growth and changes in spherical aberration.…”
Section: Discussionmentioning
confidence: 46%
“…Because the "minimum effective dose" of positive spherical aberration required to alter axial elongation in children remains unknown, further investigation of the relationship between spherical aberration and axial elongation for other optical interventions for myopia control is also warranted. A recent study 48 investigated the changes in ocular HOA with ortho-k lens wear after adjusting the compression factor (also known as Jessen factor) of a specific brand of ortho-k lens (Menicon Z Night or Menicon Z Night Toric lenses; NKL Contactlenzen B.V., Emmen, The Netherlands). The study showed that increasing the compression factor by 1.00 D significantly increased the primary spherical aberration (Z 0 4 ), RMS values of spherical aberrations, and total HOA by 40-50%, without significantly inducing more refractive changes or compromising vision in photopic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal shape asymmetry increases higher-order corneal aberrations [ 19 21 , 51 ]. Hiraoka et al found that increased corneal coma was significantly associated with decreased axial elongation in orthokeratology treatment [ 25 ].More recently, Jason et al found that positive spherical aberration associated with axial elongation in orthokeratology [ 20 ]. Jason et al suggested that the potential role of HOA, particularly spherical aberration may as the possibly mechanism of axial elongation with orthokeratology [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated strong inhibitory effects of peripheral myopic defocus on axial elongation or myopia development [ 13 15 ]. It has been proposed that changes in peripheral retina defocus [ 16 18 ] and aberrations [ 11 , 19 , 20 ](especially spherical aberrations and vertical coma) may be responsible for the reduced myopia progression reported with orthokeratology.…”
Section: Introductionmentioning
confidence: 99%
“…Nti and Berntsen review the optics of modern overnight reverse geometry orthokeratology lens designs including their effects on accommodation, peripheral refraction and on axis higher order aberrations. Lau et al also report on the change in the higher order aberration profile by modifying the Jessen factor in paediatric orthokeratology for myopia control.…”
mentioning
confidence: 99%